2006
DOI: 10.1001/archneur.63.7.1005
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual Multiple Sclerosis Pseudoexacerbations

Abstract: Background: Many women with multiple sclerosis (MS) experience transient neurologic symptom worsening and fatigue in conjunction with the menstrual cycle. Aspirin reduces MS fatigue in some patients. Objective: To describe 3 women with MS who experienced stereotypic, temperature-independent neurologic symptoms and diurnal fatigue in the mid-to-late luteal phase of the menstrual cycle. Aspirin treatment prevented the symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Because of their pharmacological profile NSAIDs have been employed for the management of side effects, when interferon beta is employed for multiple sclerosis treatment. Moreover, the classical COX1 inhibitor aspirin is frequently used to limit the severity of multiple sclerosis related fatigue and premenstrual associated pseudo-exacerbations [ [75] , [76] , [77] ]. Although COX1 in contrast to COX2 may not be considered a classical pro-inflammatory enzyme it contributes to the biosynthesis of pro-inflammatory prostaglandins [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of their pharmacological profile NSAIDs have been employed for the management of side effects, when interferon beta is employed for multiple sclerosis treatment. Moreover, the classical COX1 inhibitor aspirin is frequently used to limit the severity of multiple sclerosis related fatigue and premenstrual associated pseudo-exacerbations [ [75] , [76] , [77] ]. Although COX1 in contrast to COX2 may not be considered a classical pro-inflammatory enzyme it contributes to the biosynthesis of pro-inflammatory prostaglandins [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, relatively little is known about how NSAIDs may limit disease in MS. There are reports of clinical use of NSAIDs for MS in management of side effects associated with IFN therapies [33] and aspirin use for limiting the severity of MS-related fatigue [34] and premenstrual associated pseudoexacerbations [35]. However, these studies were not designed to test the potential for limiting demyelination in disease and there are no other reports of therapeutic effects of NSAIDs for MS.…”
Section: Discussionmentioning
confidence: 99%
“…Rarely menstrual-related relapses are described. There may also be pseudo-relapses [68]. A very early study on n = 8 relapsing MS women reported a relationship of progesterone to estradiol ratio during the luteal phase on the number and volume of contrast brain lesions.…”
Section: Mensesmentioning
confidence: 99%